GENDER: AN USEFUL CATEGORY OF ANALYSIS IN NEWSPAPERS OF THE PHYSICAL EDUCATION PRODUCED IN BRAZIL (Fiep Bulletin - online, 2014)
This study search to understand as the scientific production it is approaching the gender subjects in the school institution and in the society in that this institution this inserted. Due to that, we lifted the following subject: what does have the scientific production transmitted in newspapers of Physical Education discussed on the category gender in the school context? As corollary of that subject, it is relevant to answer: what done presuppose and do concepts on the category gender mark the production transmitted in newspapers of the Physical Education?  How has that category been located in the cultural historical context Brazilian and like it is being presented in the school institution? Starting from that initial concern, was formulated a reflection axis that was to guide us in our incursion for the selected texts: gender in the school institution while space of multiple relationships. Among the aspects discussed along this study, we pointed out mainly: the historical constitution of the category gender, the feminist movement and the emergency of the gender concept, gender and Brazilian education, gender in the school institution and the debate in newspapers of the Physical Education concerning the category gender.
Keywords: Gender; Physical Education; School institution